OC40 Is down syndrome related arthritis (DA) a distinct disease from juvenile idiopathic arthritis (JIA)?. (June 2019) - Foley, Charlene; Killeen, Orla; MacDermott, Emma; Wilson, Gerry; Floudas, Achilleas; Fearon, Ursula
Abstract : DA is frequently polyarticular-RF-negative with predominance in the small joints of the hands and wrists. It has an erosive phenotype, and clinically appears to be a more aggressive disease than JIA. Arthritis occurs more frequently in children with Down syndrome (DS), with prevalence 20 times greater than JIA. To date little is known about the underlying mechanisms that drive DA disease pathogenesis, however these features suggest that DA may be distinct from JIA. We wanted to explore this hypothesis by examining B-cell subsets and T-cell cytokine profiles; and characterising and comparing the synovial membrane immunohistochemistry in DA versus JIA. Methods: Multicolour-flow cytometry was used to analyse B and T cell phenotypes in PBMCs from 40 children (n=10/group - Healthy Control (HC), JIA, DS, DA), and assessed by Flowjo software analysis. Cells were stained as follows; B-cell panel (CD38, CD24, CD20, CD80, CD27, IgM, CD138, CD45, CD19, MHC class II, BCMA, CD40, CD86, IgD); T-cell panel - cytokines analysed after 5-hours PMA/Ionomycin stimulation (CD3, CD8, CD161, IFN-γ, TNF-α, IL-17a, GM-CSF). Synovial tissue was obtained through US-guided biopsy and analysed by immunohistochemistry for CD3, CD20, CD68, FVIII (DA n=3; JIA n=4). Levels of vascularity and lining layer hyperplasia were also scored. Analysis was performed using a semi-quantification scoring method. Results: Flow cytometry analysis revealed that children with DA had a significantly lower number of circulating CD19+CD20+ B cells when compared to children with JIA (p<0.05) and HC (p<0.001). However, they had a greater proportion of memory B cells (CD27+) when compared to children with DS (p<0.05). IFN-γ and TNF-α production by CD8+/CD8- T cells was greater in DA compared to both JIA (CD8+IFNγ+ p<0.001; CD8+TNFα+ p<0.01; CD8-IFNγ + p<0.05; CD8-TNFα p<0.05) and HC (CD8+IFNγ+ p<0.05; CD8+TNFα+ p<0.05; CD8-IFNγ+ p<0.05; CD8-TNFα p<0.01). Examination of synovial tissue demonstrated marked increase in synovial lining layer hyperplasia in DA (median 6 (3–9)) versus JIA (median 3(2–4)). Higher levels of CD3+ cells (p<0.05), Macrophages (p<0.05), CD20+ cells and FVIII in DA were also observed. Conclusion: Significant differences were observed in the immune and histological profiles of DA and JIA. These differences may begin to explain the erosive phenotype observed in DA. This study is important as it is the first of its kind to describe the immuno-histology of DA. Understanding the pathogenesis of DA will allow for more targeted, personalised treatment approaches, in turn improving outcomes and therefore quality of life for children with Down syndrome and arthritis.